Odpowiedzi

2009-12-13T17:34:14+01:00
Metodą podstawiania a nie podstawową :) a oto obliczenie
b)
2x-y=10
x+5y=-17

2x-y=10
x=-17-5y

2(-17-5y)-y=10
x=-17-5y

-34-10y-y=10
x=-17-5y

-11y=10+34
x=-17-5y

-11y=44 || :(-11)
x=-17-5y

y=-4
x=-17-5y

y=-4
x=-17-5*(-4)

y=-4
x= -17-(-20)

y=-4
x= -17+20

y=-4
x=3

c)
3m+n=9
2m-5n=-11

n=9-3m
2m-5n=-11

n=9-3m
2m-5(9-3m)=-11

n=-9-3m
2m-(45-15m)=-11

n=9-3m
2m-45+15m=-11

n=9-3m
17m=-11+45

n=9-3m
17m= 34 || :17

n=9-3m
m=2

n=9-3*2
m=2

n=9-6
m=2

n=3
m=2
1 5 1
2009-12-13T17:36:40+01:00
B)
2x-y=10
x+5y=-17

y=-10+2x
x-50+10x=-17

y=-10+2x
11x=33

y=-4
x=3

c)3m+n=9
2m-5n=-11

n=-3m+9
2m+15m-45=-11

n=-3m+9
17m=34

n=3
m=2